Coal versus coral: Australian climate change politics sees the Great Barrier Reef in court. Issue 2 (December 2021) - Konkes, Claire; Nixon, Cynthia; Lester, Libby; Williams, Kathleen
Abstract: The likelihood that climate change may destroy the Great Barrier Reef has been a central motif in Australia's climate change politics for more than a decade as political ideologies and corporate and environmental activism draw or refute connections between the coal industry and climate change. The media fuel this debate because in this contest, as ever, the news media always do more than simply report the news. Given that the Reef has also been central to the evolution of Australia's environmental laws since the 1960s, it is not surprising that the Reef is now a leading actor in efforts to test the capacity of our environmental laws to support action on climate change. In this contribution, we examine the news coverage of the Australian Conservation Foundation's (ACF) 2015 challenge to Adani's Carmichael coal mine to observe the discursive struggle between the supporters and opponents of the mine. Our analysis of the case shows that while the courts are arenas of material and symbolic contest in the politics of climate change in Australia, public interest environmental litigants struggle both inside and outside the courts to challenge the privileging of mining interests over the public interest.